2019
DOI: 10.1097/ijg.0000000000001291
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Capability of 3D Peripapillary Retinal Volume for Glaucoma Using Optical Coherence Tomography Customized Software

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Notably, our total artifact rate for glaucoma patients (61.7%) is outside the 7.1% to 58.5% range reported in the literature. [13][14][15][16][17][18][19][20][21][22] This may be due to our broad inclusion of several different types of artifacts, as opposed to only segmentation errors, which were the focus of other papers. 15,17,19,20 We discovered significant differences in the types of 3D artifacts found between glaucoma and normal patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, our total artifact rate for glaucoma patients (61.7%) is outside the 7.1% to 58.5% range reported in the literature. [13][14][15][16][17][18][19][20][21][22] This may be due to our broad inclusion of several different types of artifacts, as opposed to only segmentation errors, which were the focus of other papers. 15,17,19,20 We discovered significant differences in the types of 3D artifacts found between glaucoma and normal patients.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] However, its value is limited by a high rate of artifacts, with 7.1% to 58.5% of RNFL scans affected. [13][14][15][16][17][18][19][20][21][22] Studies show that these artifacts may cause clinically significant errors in measurement 17,23,24 and lead to false glaucoma classifications in as many as 39.0% of scans. [24][25][26] The minimum distance band (MDB) quantifies three-dimensional (3D) neuroretinal rim tissue from a high-density SD-OCT optic nerve volume scan protocol using custom-designed research software.…”
Section: Introductionmentioning
confidence: 99%
“… 32 , 33 From 3D optic nerve 193-line raster volume scans, the MDB neuroretinal rim thickness was calculated using custom-designed software. 14 16 The MDB borders were automatically detected, with the outer border ring as the RPE/BM termination or OCT-based disc boundary and the inner border ring at the ONH surface. The MDB neuroretinal rim thickness values were calculated for global values and quadrant values.…”
Section: Methodsmentioning
confidence: 99%
“…Thinning of the RNFL is associated with glaucoma. However, the greatest limitation of the RNFL thickness measurement is that its OCT measurements may be inaccurate because of artifacts in 19.9–46.3% of scans [ 24 , 25 , 26 ▪▪ , 27 ▪ , 28 ]. In an analysis of 2313 scans from 1188 patients, Liu et al defined 12 types of artifacts, which can be caused by poor data acquisition, inaccurate software analysis, or patient ocular disorder [ 28 ].…”
Section: Starting With Retinal Nerve Fiber Layer Thickness: Two-dimen...mentioning
confidence: 99%
“…Furthermore, two other studies showed that peripapillary retinal volume measurements [ 26 ▪▪ , 39 ] have excellent performance as a diagnostic tool to detect glaucoma as retinal volume is lower in OAG patients compared with normal patients. The first study used ETDRS scan circles in commercially available software packages and showed that best retinal volume parameters had similar diagnostic ability compared with best RNFL thickness parameters [ 39 ].…”
Section: Around the Optic Nerve: Peripapillary Retinal Volume Three-d...mentioning
confidence: 99%